Architects’ Perspectives on 3D Concrete Printing (3DCP) Technology in Architectural Design - Asmadinata, Azifuzaiddin; Sarpin, Norliana; Mohamed, Sulzakimin; Shafii, Haryati; Omar, Roshartini (Research in Management of Technology and Business, 2026)
The rapid urbanization and increasing demand for housing in Malaysia have intensified the need for innovative and sustainable construction technologies that enhance architectural design efficiency and flexibility. This study examines architects’ perspectives on 3D Concrete Printing (3DCP) technology in architectural design, with particular emphasis on identifying its advantages and understanding professional viewpoints on its design application. As an advanced form of additive manufacturing, 3DCP offers significant architectural benefits, including greater design freedom, reduced material wastage, improved construction precision, and the ability to realize complex forms that are difficult to achieve using conventional construction methods. Despite 3D Concrete Printing’s (3DCP) potential for sustainable and customized housing in Malaysia, its integration into architectural practice remains limited due to a critical knowledge gap regarding architects’ perceptions of design flexibility and constructability, alongside a lack of localized workflows and technical guidelines. Using a qualitative research approach, this study employs semi-structured interviews with 3 architects to identify the advantages of 3DCP technology and to analyse architects’ perspectives on its integration into architectural design practice. In alignment with Research Objective 2 (RO2), the findings reveal that architects perceive 3DCP as a transformative technology that enhances design versatility and enables the customization of complex forms. The study also highlights how 3DCP improves sustainability through reduced material waste and strengthens the integration between digital design tools and physical construction processes. This study contributes to the existing body of knowledge by providing an architectural-oriented understanding of 3DCP, positioning the technology as a design-driven innovation rather than solely a construction technique. The findings aim to assist architects, designers, and built environment professionals in making informed decisions regarding the adoption of 3DCP in future architectural design and housing developments in Malaysia.